2022
DOI: 10.1590/fst.82621
|View full text |Cite
|
Sign up to set email alerts
|

Determining the amount and bioaccessibility of methylglyoxal and glyoxal in functional snack foods with herbal teas: effect of different herbal teas on α-Dicarbonyls

Abstract: The global challenge against cardiovascular diseases, some tumours, diabetes, and diabetes-related disorders have accelerated. These conditions are often due to several dysfunctions in the metabolic pathway, which are influenced by diet. One reason for this is that excess consumption of processed foods may be accompanied by conversion of their components into harmful macromolecules such methylglyoxal (MGO) and glyoxal (GO) in the body. These hazardous compounds can be restricted during metabolism by plant-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was shown that MG was trapped by taxifolin and its metabolites in mice urine and fecal samples, in a dose-dependent manner [ 137 ]. The analysis of an in vitro simulated digestion of a snack food (containing glucose, fructose, and sucrose) showed that digestion especially increased levels in glyoxal, which decreased when incubating with three different beverages (green tea, bergamot-flavored black tea, and olive-leaf tea) [ 138 ].…”
Section: Phenolic Compounds and Their Effect On Dicarbonyl Compounds ...mentioning
confidence: 99%
“…It was shown that MG was trapped by taxifolin and its metabolites in mice urine and fecal samples, in a dose-dependent manner [ 137 ]. The analysis of an in vitro simulated digestion of a snack food (containing glucose, fructose, and sucrose) showed that digestion especially increased levels in glyoxal, which decreased when incubating with three different beverages (green tea, bergamot-flavored black tea, and olive-leaf tea) [ 138 ].…”
Section: Phenolic Compounds and Their Effect On Dicarbonyl Compounds ...mentioning
confidence: 99%